Study of mechanical properties of lithium ion pouch cells - Parthasarathy Chethan (2016)
Increasing demand for energy, concerns on energy security and ever reducing the stock of petroleum has led to an approach which has led us to explore non-conventional forms of energy, thereby diversifying the sources of energy. The potential of renewable sources of energy are being tapped extensively, which would need equipment such as energy storage devices for its smooth operations, where batteries play an important role. Similarly, electric vehicles are gaining prominence, where rechargeable batteries are must for its implementation. Lithium polymer pouch cell is naturally the best choice for such large scale energy storage applications, due to its packaging efficiency & higher energy density. It is imperative to perform extensive characterization of lithium polymer pouch cells, to study its behavior in various operating conditions. Elaborate studies have been conducted on temperature characterization, different C-rating charge and discharge characterization of pouch cells & their relationships are well established. However, studies on the effect of external pressure on pouch cells and their characterization with temperature & varying C-rates are less common. The aim of this thesis is to establish characteristics of Lithium polymer pouch cells when external pressure is applied on it, emphasizing particularly on capacity variations in such an atmosphere. A test rig was built for this purpose, and pouch cells were comprehensively studied and characterized by external pressure being applied over it. The tests were conducted with 1C charge current employing CC/CV scheme and constant 1C discharge current. The test cases were parameterized with varying external pressures applied on the battery and with two temperature conditions- room temperature & 45C and were specifically designed to study the changes in capacity in such conditions. Pulse power tests were conducted to study the effects of external pressure on the Open circuit voltage of pouch cells.